Energy efficient node addressing scheme in self-organised sensor networks. (1st December 2008) - Teng, Rui
Sensor networks are envisioned to support autonomous and spontaneous networking for a wide range of applications such as environment monitoring. Due to energy constraints, it is difficult for wireless sensor nodes to handle heavy protocol stacks with a large protocol overhead. In this paper, we present a novel address auto configuration scheme, which we call SMallest-size sensor AddRess auToconfiguration scheme (SMART), to configure potential shortest-size local unique addresses for sensor networks with energy efficiency. SMART achieves energy efficiency in three ways. First, it automatically configures node address within a potential smallest address space for a number of sensor nodes, in order to achieve the small address size. Second, it avoids address conflicts during the address configuration. Third, it configures addresses with a small configuration overhead and achieves load balance among sensor nodes.